Multidimensional poverty in Colombia, 1997 - 2010 - Beatriz Yadira Diaz; Roberto Carlos Angulo Salazar; Renata Pardo Pinzon (University of Essex, Institute for Social and Economic Research (ISER), 2013)
This paper presents the Colombian Multidimensional Poverty Index (CMPI), an initiative of the National Planning Department based on the methodology of Alkire and Foster (2010). The proposed index for Colombia is composed of five dimensions: education of household members; childhood and youth conditions; health; employment; and access to household utilities and living conditions. A nested weighting structure was used, where each dimension is equally weighted, as is each indicator within each dimension. Analysis of the results demonstrates that multidimensional poverty in Colombia decreased between 1997 and 2010. Multidimensional poverty rates decreased in both urban and rural areas, but imbalances remain. As well as calculating the incidence of multidimensional poverty, we also calculate measures of the poverty gap and the severity of poverty. The reduction in severity is larger than the reduction in the gap, suggesting that the depth of poverty among the poorest has been reduced through targeting. In addition, this paper presents some public policy applications of the CMPI.
Keywords: I32; D63; O20; 330; multidimensional poverty; Colombia; Alkire and Foster measures; deprivation; urban / rural disaggregation; inequality